Towards living a better future: political vision and the humanistic conscience - Morelock, Jeremiah; Narita, Felipe Ziotti [UNESP]; Ward, Crystal Lee (Bristol University Press, 2024)
Fromm’s theories can help the Left overcome its collective rejection of individualism and universalism, which limit socio-political possibility, offering Left solutions to these challenges and promoting alternate perspectives. His humanistic vision shares much with humanistic and positive psychology but differs in important respects. Centrally, Fromm’s notion of emancipation emphasises both individual and societal components. He believes independent and authentic relationships are a higher expression of human potential and bring true fulfilment. Fromm identifies a creative, non-alienated character orientation that includes a ‘humanistic conscience’. Comparing authoritarian and humanistic consciences, he emphasises human potential and social and individual interdependence. Personal development must also drive social change, and vice versa. Fromm’s perspective rejects zero-sum, either/or thinking about social change vis-à-vis individual flourishing. For him, both are important, and they are related. Following Fromm’s example, the Left should stress that individualistic societies cannot satisfy individual needs. Self-fulfilment requires fairness, community and shared personal experiences.
Keywords: ethics; individualism; liberation